POSBINDU PTM (PENYAKIT TIDAK MENULAR) KEPADA MASYARAKAT LANSIA DI DESA SIBANGKUA ANGKOLA BARAT TAHUN 2021 - Diningsih, Ayus (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
Empowerment of elderly self-health in Sibangkua Village can be started through the role of Posbindu Elderly Students of KKN Group III Aufa Royhan University in Padangsidimpuan City. Posbindu activities encourage the empowerment of the elderly to increase health awareness. The aims of this study were to 1) describe the Posbindu Elderly program; 2) identify the health condition of the elderly in Sibangkua Village; 3) analyze the achievement of the principle of empowerment; 4) and analyze the impact and response of the community regarding the Posbindu Elderly Program. Data collection methods in this study were obtained through observation, interviews, documentation studies, and direct practice of health checks. The results showed that the self-health empowerment program for the elderly at the Elderly Posbindu for KKN Students Group III at Aufa Royhan University in Padangsidimpuan City included health checks, elderly exercise, and health socialization. The program plays a role in improving the health condition of the elderly which can be said to be in good health and there are no complaints of serious diseases, only a few elderly have complaints of non-communicable diseases (PTM). The implementation of the empowerment principle has also been achieved in an effort to empower the health of the elderly. The impact obtained from the Posbindu program for KKN Students Group III at Aufa Royhan University in Padangsidimpuan City is that respondents become more aware of health problems so that they pay more attention to their daily lifestyle. The role of Posbindu Student Community Service Program at Aufa Royhan University in Padangsidimpuan City Group III in empowering the health of the elderly also received a positive response from the community.